Role of transmembrane protein 33 in tumorigenesis and development - LOU Haijun, MENG Menggen, ZHANG Zhenyu, TONG Zhuoyun, WUDU Muli (Jichu yixue yu linchuang)
Transmembrane protein 33 (TMEM33) is up-regulated in the majority of cancers. To change the expression of TMEM33 can significantly affect the proliferation, migration, and invasion of renal and cervical cancer cells. Its mechanisms of action may involve four aspects: 1)participation in lipid metabolism; 2)regulation of endoplasmic reticulum; 3)regulation of intracellular calcium homeostasis; 4) participation in angiogenesis.